2022
DOI: 10.1590/1678-4685-gmb-2021-0215
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito long non-coding RNAs are enriched with Transposable Elements

Abstract: Long non-coding RNAs (lncRNAs) lack coding capacity and mounting evidence suggests that they have a regulatory role in diverse organisms. Most knowledge about lncRNAs comes from studies on vertebrates, including a structural association between lncRNAs and transposable elements (TEs). TE sequences are genomic parasites found in all branches of life and are particularly active and abundant in insect genomes. Here we investigate the contribution of TEs to lncRNA biogenesis in Aedes albopictus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We previously observed that some TE-derived lncRNAs function as regulators of genes involved in the antiviral response of Ae. albopictus (105). However, it seems that, in Ae.…”
Section: Relationship Of Immune Response Viral Infection and Te Expre...mentioning
confidence: 98%
“…We previously observed that some TE-derived lncRNAs function as regulators of genes involved in the antiviral response of Ae. albopictus (105). However, it seems that, in Ae.…”
Section: Relationship Of Immune Response Viral Infection and Te Expre...mentioning
confidence: 98%